Przedsi\~nebiorstwo w uj\~neciu menedçzerskich teorii firmy; Enterprise According to Managerial Theories of the Firm - Elzbieta Rogalska (Institute of Economic Research (IER), 2013)
– The dominant role of corporations in modern economy and observed widespread oligopolization are the sources of practical need for the theoretical concept of the enterprise explaining the operations of large companies, with a particular focus on their primary objectives and aims, and the role they play in the markets. In this paper three concepts of the enterprise are discussed that take into account the changing conditions of the company. All the discussed concepts were formulated based on the managerial theory approach: the model of an enterprise that maximizes the sustainable growth rate of R. Marris, the model of an enterprise that maximizes revenue from the sales of W.J. Baumol and the model of O.E. Williamson that describes the preferences of managers in discretionary decision-making process. The aim of the publication is to present the managerial theory of the firm, which is alternative to traditional neoclassical concept of enterprise, their critical evaluation and an indication of application possibilities.
Keywords: D21; D24; 330; balanced rate of growth of the firm; Penrose effect; expense preference; interdependence of decisions